Importance And Significance of International Student Assessment Programs Pisa and TIMSS in Education (Pedagogical Cluster-Journal of Pedagogical Developments, 2024)
This article reflects information about the importance of the international assessment programs PISA and PIRLS, which are foreign experience, in improving the quality of education and achieving efficiency